Numerical Simulation of Wind Waves and calculation of planning wave factors in the East Taihu Lake, Jiangsu Province, China. Issue 1 (August 2021) - Jun, Chen; Fan, Zhu; Xiang, Lin
Abstract: Taihu Lake is a large shallow lake in the lower Yangtze River Delta. The wave action in Taihu Lake plays an important role in coastal port construction. In this paper, based on the 10 min average wind speed at 10 m above the water surface recorded hourly from August 14 to August 17, 2014, the SWAN wave model is used to simulate the wind waves of the Taihu Lake in the corresponding period. Due to the lack of long-time series of wave observation data in the project area, the relationship between design wind speed and wind wave is used to calculate wave elements in different return periods. The results show that the strong wind direction and strong wave direction of the East Taihu Lake are NNW. The waves in the proposed Qidu harbor are mainly from the waves outside the permeable breakwater. Under the action of the most unfavorable wave direction NE, the effective wave height of most waters in the harbor is below 0.4m, which can meet the requirements of avoiding waves for fishing boats.